Evaluation of the Flexural Rigidity of Underground Tanks Manufactured by Rotomolding - Oldřich Šuba; Ondřej Bílek; Milena Kubišová; Vladimír Pata; Dagmar Měřínská (Applied Sciences, 2022)
This study focuses on the flexural properties of the layered wall structures of plastic tanks produced by rotational molding technology. The aim was to assess the possibility of replacing the homogeneous walls of rotationally cast large-volume underground tanks with structural walls for stability and warpage prevention. The possibilities of material saving by combining lightweight and non-lightweight tank wall layers were investigated. By applying the engineering theory of bending inhomogeneous layered walls, the flexural rigidity values of the walls of the tanks of different structures were determined. The values of the flexural rigidity of the tank wall samples produced by rotomolding technology were determined experimentally. Moreover, a comparison of the calculated and experimentally determined flexural rigidity values of the layered walls and optimization of these structures was carried out. In the case under study, it was theoretically and experimentally confirmed that the optimum ratio of compact layer thickness versus total wall thickness is given by the resulting value: t1OPT = 0.189 h.